Application of the RE-AIM framework to evaluate the implementation of telehealth pulmonary rehabilitation in a randomized controlled trial among African-American and Hispanic patients with advanced stage Chronic Obstructive Pulmonary Disease - Jennifer Polo; Melissa J. Basile; Meng Zhang; Keyla Ordonez; Danielle Rodriguez; Eugenia Boye-Codjoe; Myia Williams; Donna Tsang; Richard Medina; Sonia Jacome; Parvez Mir; Sameer Khanijo; et al. (BMC, 2023)
Abstract Background Pulmonary rehabilitation (PR) decreases rehospitalization for people with COPD. However, less than 2% receive PR, partly due to lack of referral and sparsity of PR facilities. This disparity is particularly pronounced in African American and Hispanic persons with COPD. Telehealth-provided PR could increase access and improve health outcomes. Methods We applied the RE-AIM framework in a post-hoc analysis of our mixed methods RCT comparing referral to Telehealth-delivered PR (TelePR) versus standard PR (SPR) for African American and Hispanic COPD patients hospitalized for COPD exacerbation. Both arms received a referral to PR for 8 weeks, social worker follow-up, and surveys administered at baseline, 8 weeks, 6, and 12 months. PR sessions were conducted twice a week for 90 min each (16 sessions total). Quantitative data were analyzed using 2-sample t tests or nonparametric Wilcoxon tests for continuous data and χ2/Fisher exact tests for categorical data. Logistic regression-estimated odds ratios (ORs) were used for the intention-to-treat primary outcome. Qualitative interviews were conducted at the end of the study to assess adherence and satisfaction and were analyzed using inductive and deductive methods. The goal was to understand Reach (whether the target population was able to be enrolled), Effectiveness (primary outcome was a composite of 6-month COPD rehospitalization and death), Adoption (proportion of people willing to initiate the program), Implementation (whether the program was able to be executed as intended, and Maintenance (whether the program was continued). Results Two hundred nine people enrolled out of a 276-recruitment goal. Only 85 completed at least one PR session 57/111 (51%) TelePR; 28/98 (28%) SPR. Referral to TelePR compared to SPR did not decrease the composite outcome of 6-month COPD-readmission rate/death (OR1.35;95%CI 0.69,2.66). There was significant reduction in fatigue (PROMIS® scale) from baseline to 8-weeks in TelePR compared to SPR (MD-1.34; ± SD4.22; p = 0.02). Participants who received TelePR experienced improvements from baseline in several outcomes (ie, before and after 8 weeks of PR) in the following: COPD symptoms, knowledge about COPD management, fatigue, and functional capacity. Among the patients who had 1 initial visit, adherence rates were similar (TelePR arm, 59% of sessions; SPR arm, 63%). No intervention-related adverse events occurred. Barriers to PR adoption included difficulty or reluctance to complete medical clearances and beliefs about PR efficacy. Notably, only 9 participants sustained exercise after program completion. Maintenance of the program was not possible due to low insurance reimbursement and sparsity of Respiratory Therapists. Conclusions TelePR can reach COPD patients with health disparities and can be successfully implemented. The small sample size and large confidence intervals prevent conclusion about the relative effectiveness of participating in TelePR compared to SPR. However, improved outcomes were seen for those in TelePR as well as in SPR. Increasing adoption of PR and TelePR requires consideration of comorbidity burden, and perception of PR utility, and must facilitate medical clearances. Given the sparsity of SPR locations, TelePR can overcome at least the barrier of access. However, given the challenges to the uptake and completion of PR - many of the additional barriers in PR (both in TelePR and SPR) need to be addressed. Awareness of these real-world challenges will not only inform implementation of TelePR for clinicians seeking to adopt this platform but will also inform study designers and reviewers regarding the feasibility of approaches to patient recruitment and retention.